The Relationship between the Application of Entrepreneurship Education and Family Environment with Entrepreneurial Interest of Politeknik Pelayaran Barombong Cadets - Masluhah, Masluhah; Arifin, Moh. Zainal; Pratama, Putu Peby; Amin, Ahmad; Wisudawanto, Feri (PT. EQUATOR SINAR AKADEMIA, 2025)
Being in an educational environment that produces a generation of strong sailors makes the mindset of the cadets of the Politeknik Pelayaran (Poltekpel) Barombong is to become sailors. It is the same with parents who send their children to Poltekpel to become sailors. However, this is not the basis for ignoring entrepreneurship education. This is because they will not always be at sea, there is a time when they will think about how to continue their lives without having to sail with the money they have collected. This is where entrepreneurship science plays an important role. The research used quantitative research methods. The data collection technique was carried out by questionnaire. The analysis technique is descriptive statistics. The analytical tool used is SmartPLS software version 3.0. The results showed the relationship of entrepreneurship education with entrepreneurial interest in the strong category, meaning that the higher the application of entrepreneurship education for students, the higher the interest in entrepreneurship. Second, the relationship between family environment and entrepreneurial interest in the strong category, which means that the higher the family environment supports entrepreneurship, the higher their entrepreneurial interest, and vice versa if the family environment does not provide support for entrepreneurship in cadets, then the entrepreneurial interest of Poltekpel cadets will be lower. Third, entrepreneurship education and family environment together with cadets' entrepreneurial interest have a strong relationship. simultaneous contribution of entrepreneurship education variables (X1) and family environment (X2) with entrepreneurial interest (Y) is fifty percent more while the rest is determined by other variables outside the study. Poltekpel cadets although basically their ultimate goal is to become sailors as expected by the family but they are also interested in entrepreneurship. They have a plan, namely by working as sailors for four or seven years after enough money has been collected for business capital, they plan to open a new business.